Fabrication of homogenously self-alignment fringe-field switching mode liquid crystal cell without using a conventional alignment layer. Issue 9 (15th July 2017) - Mizusaki, Masanobu; Tsuchiya, Hiroshi; Minoura, Kiyoshi
ABSTRACT: We propose a novel method to fabricate a uniaxially homogeneous alignment of liquid crystal (LC) molecules without using a conventional alignment layer such as polyimide film. The method produces the polymer alignment layer (PAL) by polymerisation of the monomer including in the LC layer above the TNI of the LC material. The fringe-field switching (FFS) mode LC cell with the PAL (FFS-PAL-LC cell) produced from the monomer 4, 4ʹ-di-mehacryloyl-oxy chalcone (4, 4ʹ-DMOCh) exhibited enough level of alignment state and electro-optical property compared with the FFS-LC cell having the conventional polyimide-type alignment layer. We can expect that the FFS-PAL-LC cell is useful for next-generation displays such as flexible liquid crystal displays (LCDs) because the method does not need high-temperature process of over 200°C. Graphical Abstract: